The Impact of Artificial Intelligence on Social Problems and Solutions: An Analysis on The Context of Digital Divide and Exploitation - Ahmet Efe (Yeni Medya)
Continued advances in artificial intelligence (AI) technology innovations include ever-wider aspects of modern society’s economic, cultural, religious, and political life via new media tools and communication techniques. Considering AI as part of technological tools, networks, and institutional systems, innovative technology can be essential in solving social problems. With such a mindset, this study done on literature knowledge and sectoral research reports aims to capture AI’s expanding role and impact on social relations by expanding its ethical understandings and conceptual scope. The study tries to answer, if recent innovations in AI herald unprecedented social transformations and new challenges. This article critically assesses the problem, challenging the unending innovative technological determinism of many debates and reframing related issues with a sociological and religious approach. The study focuses on the importance of theoretical discussing the relationship between specificity and ecological validity of algorithmic models and how AI modeling is an essential contribution to the methodological approaches of scientists interested in social phenomena.